(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2016)
Career guidance is one of the most important processes in the lives of students currently studying at universities of educational sciences. It helps the teaching community to facilitate, through its guiding role, their professional identity and self-determination in order to ensure they remain in their chosen career. The Educational Revolution calls for a new style of work from administrators and teachers, in which the diversity and individuality of each student must be addressed and the results of educational work must be taken to higher levels.